The effectiveness of VAT and GST implementation in enhancing tax revenue: A comparative analysis - Wijaya, Suparna; Syafitri, Noviyantini Nasywa; Ananda, Michele Tri; Febriani, Syifa Listi; Adli, Najwa Nabila; Raihana, Naura (Jurnalku, 2025)
This article evaluates the effectiveness of Value-Added Tax (VAT) and Goods and Services Tax (GST) implementation in enhancing national tax revenue. Through a systematic review and analysis of research studies from various countries that have adopted VAT/GST systems, this study demonstrates that both tax mechanisms significantly contribute to increasing tax revenue by expanding the tax base and reducing potential tax leakage. While their effectiveness varies across countries based on implemented policies, key factors such as taxpayer compliance rates, administrative complexity, and technological utilization in tax collection substantially impact implementation success. The findings emphasize the importance of well-designed policy formulation tailored to local economic contexts to ensure that VAT and GST can optimally contribute to national revenue. This research provides valuable insights for policymakers considering tax system reforms aimed at improving fiscal sustainability.